The influence of chitin structure on its enzymatic deacetylation - Jaworska Malgorzata M.; Roberts George A.F. (Chemical and Process Engineering)
The possibility of producing chitosan by enzymatic deacetylation of chitin has been the subject of numerous investigations over the last twenty years, but to date no satisfactory method has been developed. In this paper the influence of chitin chain conformation and chitin particle crystallinity on the enzymatic deacetylation of chitin is investigated to determine the relative importance of these two factors on the process. It is shown that the high crystallinity of chitin is the main obstacle to converting chitin to chitosan by enzymatic deacetylation.